You are on page 1of 15

# Ordinary Differential Equations [FDM 1023]

Chapter 2

Chapter 2:

## First-Order Differential Equations

Overview
2.1. Separable Variables 2.2. Linear Equation 2.3. Exact / Non-Exact Equation 2.4. Homogeneous Equation 2.5. Bernoulli Equation

## 2.1. Separable Variables

Learning Outcome
At the end of this section you should be able to: Identify and solve a separable DE.

## 2.1. Separable Variables

Definition
General form of the first-order DE , , = 0

## 2.1. Separable Variables

Definition
A first-order DE of the form

dy = g ( x)h( y ) is dx

## 2.1. Separable Variables

Examples
dy 1) = y 2 xe3 x + 4 y dx
Indeed, is separable

dy = y 2 xe3 x + 4 y dx

= y 2 xe3 x e 4 y 3x 2 4y = xe y e = g ( x ) h( y )

)(

dy 2) = y + sin x dx

is not separable

## 2.1. Separable Variables

Method of Solution
Step 1: Divide the both sides of the separable DE

with

h( y ) .

= ()

1 where = . ()

## 2.1. Separable Variables

Step 2: From the form of

## We have to integrate both sides of the equation

=
Combine and , thus

+ = +

= + ,

( = )

## 2.1. Separable Variables

Example 1
Solve the given DE,
Solution:

= =

## 2.1. Separable Variables

Step 2: Integrate the both sides

= = 1 1 = + 3 = 1 + 3 1

## 2.1. Separable Variables

Example 2
dy Solve the DE, (1 + x ) =y dx
Solution: Step 1: Separate the variables

dy (1 + x ) = y dx
dy dx = y 1+ x

## 2.1. Separable Variables

Step 2: Integrate the both sides

dy dx = y 1+ x
dy dx y = 1+ x
ln y = ln x + 1 + c
y =e
ln x +1 + c

ln y = ln x + 1 + ln c ln y = ln (c x + 1 ) y = c x +1

y =e
ec = d

ln x +1 c

y = d x +1

y = c(x + 1)

y = d (x + 1)

## 2.1. Separable Variables

Example 3
Solve the DE,

dy x = dx y

y (4) = 3

Example 4
Solve the DE,

dy y cos x = e y sin 2 x dx

y (0 ) = 0

## 2.1. Separable Variables

Exercise 2.1
Solve the following DE by separation of variables:

dy 1) = sin 5 x dx dy 2 2) = ( x + 1) dx

dx 1 + 2 y 2 5) = dy y sin x
.

3) dx + e dy = 0

3x

dy 6) = e3x+2 y dx 2
dy 2 y + 3 7) = dx 4 x + 5
dy y 2 1 8) = 2 , y (2 ) = 2 dx x 1

4)dx x 2 dy = 0